Integrated anaerobic/aerobic bioprocess environments and the biodegradation of complex hydrocarbon wastes - Ehlers, George A C (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
An investigation of the biodegradation of complex hydrocarbon wastes, with emphasis on chlorinated aromatic compounds, in an anaerobic/aerobic bioprocess environment was made. A reactor configuration was developed consisting of linked anaerobic and aerobic reactors which served as the model for a proposed bioremediation strategy targeting subterranean soil/sediment/aquifer chlorinated phenol-contaminated environments. Here oxygen is frequently limited and sulphate is readily available, as occurs especially in marine sediment and intertidal habitats. In the anaerobic system the successful transformation and mobilization of the model contaminant, 2,4,6-trichlorophenol, was shown to rely on reductive dechlorination by a sulphate-reducing dependent dechlororespiring co-culture. This was followed in the aerobic system by degradation of the pollutant and its metabolites, 2,4-dichlorophenol, 4-chlorophenol and phenol, by immobilized white-rot fungi.The strategy was initially investigated separately in laboratory bench- and intermediate scale reactors whereafter reactors were linked to simulate the integrated biodegradation strategy. The application of the fungal reactor to treat an actual waste stream by degrading complex mixtures of hydrocarbons in a waste oil recycling effluent was also investigated. The mineralization of phenol and 2,4,6-TCP by immobilized fungal cultures was studied in pinewood chip and foam glass bead-packed trickling reactors. The reactors were operated in sequencing batch format. Removal efficiency increased over time and elevated influent phenol and TCP (800 and 85 mg.Lâ »Â¹) concentrations were degraded by > 98 % in 24 "“ 30 h batch cycles. Comparable performance between the packing materials was shown. Uptake by the packing was negligible and stripping of compounds induced by aeration had a minimal effect on biodegradation efficiency. Reactor performances are discussed in relation to sequencing batch operation and nutrient requirements necessary to sustain fungal activity in inert vs. organic material packed systems. It was shown that a co-culture consisting of sulphate-reducing and dechlororespiring bacteria established in fed-batch and soil flasks, as well as pine chip-packed fluidized bed reactors. Results showed reductive dechlorination of 2,4,6-TCP to be in strict dependence on the activity of the sulphate-reducing population, sulphate and lactate concentrations. Transformation to 2,4-DCP, 4-CP and phenol was enhanced in sulphate deficient conditions. Dechlororespiring activity was found to be dependent on the fermentative activity of sulphate-reducing bacteria, and the culture was also shown to mobilize and dechlorinate TCP in soils contaminated with the pollutant. Linking the systems achieved degradation of the compound by > 99 % through fungal mineralization of metabolites produced in the dechlororespiring stage of the system. pH correction to the anaerobic reactor was found to be necessary since acidic effluent from the fungal reactor inhibited sulphate reduction and dechlorination. The fungal reactor system was evaluated at intermediate-scale using a complex waste oil recycling effluent. Substantial COD reduction (> 96 % in 48 h batch cycles) and removal of specific effluent hydrocarbon components was shown in diluted, undiluted (COD > 37 g.Lâ »Â¹) and 2,4,6-TCP-spiked effluents. Industrial application of the fungal reactor was evaluated in a 14 mÂ³ pilot plant operated on-site at a waste oil processing plant.
Keywords: Hydrocarbons -- Biodegradation; Sewage -- Purification -- Anaerobic treatment; Water -- Purification -- Biological treatment; Anaerobic bacteria; Aerobic bacteria